21 lessons for the 21st century - Harari,Yuval Noah. (New York Spiegel & Grau, 2018)
How do computers and robots change the meaning of being human? How do we deal with the epidemic of fake news? Are nations and religions still relevant? What should we teach our children?
Includes bibliographical references and index.
Keywords: Civilization, Modern--21st century